Conservation and development guidelines for the extension of art and culture in Nam Phon village area Chiang Khan District, Loei Province - Phoungmanee, Thairoj; Charoensuk, Kodchasri; Laokonka, Pongpat; Ajanathorn, Naiyana (Journal of Fine and Applied Arts Khon Kaen University, 2021)
This research article, the faculty of researchers, uses the qualitative research methodology in the study. The objective is to 1) study the area and context of Ban Nam Phon art and culture, Chiang Khan District, Loei Province, and 2) to study conservation and development guidelines for the art and culture of Ban Nam Phon, Chiang Khan District, Loei Province. The target population of 24 people in the research has come up with a specific method, using document studies, interviews and meetings as a tool and data collection method. Analyze data by content analysis Present data with analytical depictions. The results showed that: 1) Ban Nam Phon is a village in Chiang Khan District, Loei Province. The village has been established since 1875, with four people surveying the area, and 36 families have been evacuated. The art of the water house culture is distinguished and unique, namely the show of the liver, which has been passed down for more than 100 years, with government agencies and educational institutions constantly gaining knowledge and understanding of the value of cultural art. As a result of the development of education and society, the community lacks interest in the existing arts and culture, which only a small group of people try to inherit. 2) The approach to the preservation and development of the art and culture of Ban Nam Phon, the potential government agencies both in and out of the area, must enter into the recognition and appreciation process to raise awareness of the art culture that is about to disappear. (2) the establishment of a community-based conservation group or tourism management group, (3) studying community work, master conservation and extension of the arts and culture; (6) Education, Research Compiled to create a variety of media for publishing, and (7) Creating a group of youth in the area to have communication skills and cultural art for welcoming tourists.